THE TRANSFORMATION OF SCHOOL PRINCIPAL LEADERSHIP IN DEVELOPING STUDENTS’ LITERACY CULTURE AT SMP NEGERI 1 SIANTAN - Aminudin Busra; Nunu Mahnun (SOSIOEDUKASI, 2026)
This study aims to examine the transformation of school principal leadership in developing students’ literacy culture at SMP Negeri 1 Siantan. The main issue addressed in this research is the relatively low level of students’ literacy, which remains a significant challenge in improving educational quality. School leadership plays a strategic role in integrating literacy programs systematically and sustainably within the school environment. This study employed a qualitative approach with a descriptive design. The participants consisted of a principal, teachers, and students selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the transformation of school principal leadership is reflected in the strengthening of literacy-oriented vision, the development of innovative literacy programs, the enhancement of collaboration among teachers and stakeholders, and the creation of a conducive literacy environment. Transformational leadership was found to significantly improve students’ engagement in literacy activities. However, several challenges remain, including limited resources and initially low reading interest among students. This study concludes that school principal leadership plays a crucial role in fostering a sustainable literacy culture in schools.